Analisis Isi Penyampaian Pesan Dakwah Toleransi Log-in Melalui Podcast Youtube Deddy Corbuzier - Anisa, Ayu; Suryasuciramdhan, Arfian; Zulfikar, Meiby; Dwiyanti, Shafira; ., Suminah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Da'wah can be interpreted as a process of conveying or inviting someone consciously to embrace, study, and practice religious teachings, so as to awaken, restore the potential benefits of others that literally every human being should have. (Hilmi Sha'bani et al., 2024). Rapid technological development, the delivery of da'wah is intensively carried out through social media such as YouTube. Its broad scope of messages can be conveyed by reaching out to many masses from different cultures and religions. The author tries to "Analyze the Content of Delivering the Message of Da'wah Tolerance" #LogInCloseTheDoor on Youtube Deddy Corbuzier hosted by Habib Ja'far and Onad, in the last episode by inviting 6 religious leaders, namely Islam, Buddhism, Catholicism, Christianity, Confucianism, and Hinduism. Aims to explore an objective understanding of the value of delivering the message of da'wah tolerance of various religions in Indonesia through Youtube on the Log-in podcast. The research uses qualitative approach methods, with descriptive techniques, through the application of documentation data collection, literature studies and content analysis. With the results to provide an understanding of how the message of tolerance in each religion in Indonesia can show the value of togetherness, diversity, and unity, explaining the role of YouTube social media in Log-in content is an upgrade of the way of preaching with a relaxed language style can have a positive impact on society.